The biological mechanisms and impact pathways of nitrogen input on the forest soil nitrous oxide emissions - Chen, Guangshui; Yang, Zhijie (Geographical Research Bulletin, 2025)
Forest soil is a significant source of atmospheric nitrous oxide (N₂O), and its emission processes are strongly influenced and regulated by nitrogen input. This review systematically summarizes the primary mechanisms of N₂O production in forest soils, including nitrification, denitrification, and non-biological pathways, and elucidates the role of environmental factors, such as soil physicochemical properties and climatic conditions, in regulating N₂O emissions. It highlights the biological pathways through which nitrogen input affects N₂O emissions via plants and soil microorganisms, including plant nitrogen uptake and allocation, litter decomposition processes, the regulatory role of arbuscular mycorrhizae, and the contribution of soil microbial functional gene abundance and diversity to N₂O production pathways. Additionally, the review analyzes the indirect effects of nitrogen input on critical factors such as soil moisture and substrate concentration and compares the differences and driving mechanisms of various nitrogen forms on N₂O production pathways. This study aims to deepen the understanding of how nitrogen input regulates forest soil N₂O emissions through multidimensional pathways, providing a scientific basis for optimizing nitrogen management in forest ecosystems and developing greenhouse gas mitigation strategies.